RIGHT TO INFORMATION AND GOOD GOVERNANCE: A STUDY OF THE IMPACT OF RTI ON TRANSPARENCY AND ACCOUNTABILITY IN INDIAN ADMINISTRATION - Pantawane, Jayashree; Butle, Abhay (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Right to Information (RTI) Act, 2005, is a pivotal legislation in India that empowers citizens to access information held by public authorities, fostering transparency and accountability in governance. This study examines the impact of RTI on good governance in the Indian administrative framework, focusing on its role in enhancing transparency, reducing corruption, and increasing public accountability. The research evaluates the effectiveness of RTI implementation, highlights challenges faced by stakeholders, and suggests measures for its optimization. The study underscores RTI as a vital tool for participatory democracy and good governance.